CEOs Under Fire: The Effects of Competition from Inside Directors on Forced CEO Turnover and CEO Compensation - Mobbs, Shawn (Journal of Financial and Quantitative Analysis, 2013)
Abstract This study examines board monitoring when a credible chief executive officer (CEO) replacement is on the board. Inside directors whose talents are in greater demand externally, as reflected by their holding outside directorships, are more likely to become CEOs, and their presence is associated with greater forced CEO turnover sensitivity to accounting performance and CEO compensation sensitivity to stock performance. These results reveal that certain insiders strengthen board monitoring by serving as a readily available CEO replacement and contradict the presumption that all insiders are under CEO control. Furthermore, the results persist when accounting for the endogenous firm selection of talented inside directors.